Pola Modernisasi Pendidikan Islam Di Pondok Pesantren Mamba’ul Hikmah Kendal Jawa Tengah - Ahmad Munadirin; Eko Sariyekti; Husna Nashihin; Triana Hermawati (At Turots: Jurnal Pendidikan Islam, 2022)
This research is classified as library research research. The background of this research lies in the reason that Islamic boarding schools should be able to develop their pesantren education models, in fact there are still many pesantren education that have not been able to develop so that they are suspended animation. There are four important points that will be the focus of this research, first, the profile of the Mamba'ul Hikmah Kendal Islamic Boarding School. Second, the typology of Islamic education at the Mamba'ul Hikmah Kendal Islamic Boarding School. Third, the development strategy of the Mamba'ul Hikmah Kendal Islamic Boarding School. Fourth, the advantages and disadvantages of developing the Mamba'ul Hikmah Kendal Islamic Boarding School. This research shows that first, the success of the establishment of this Islamic boarding school cannot be separated from the factor of community satisfaction with the teaching conducted by Dr. Kh. Suyuthi Murtadlo.